Monetary Policy and Nominal Rigidities under Low Inflation - Steinar Holden (Center for Economic Studies and ifo Institute (CESifo), 2001)
In most European countries, money wages are given in collective agreements or individual employment contracts, and the employer cannot unilaterally cut wages, even after the expiration of a collective agreement. Ceteris paribus, workers have a stronger bargaining position when they try to prevent a cut in money wages. If inflation is so low that some money wages have to be cut, workers stronger bargaining position requires higher unemployment in equilibrium. However, inflation is more stable when money wage rigidity binds, providing an incentive for monetary policy makers to choose a low target for inflation, which is easier to fulfil.
Keywords: 330; Nominal wage rigidity; labour contracts; monetary policy; inflation; equilibrium unemployment